Impact of Platelet Count on Perioperative Bleeding in Patients With Cirrhosis Undergoing Surgical Treatments of Liver Cancer - Ronca, Vincenzo; Barabino, Matteo; Santambrogio, Roberto; Opocher, Enrico; Hodson, James; Bertolini, Emanuela; Birocchi, Simone; Piccolo, Gaetano; Battezzati, PierMaria; Cattaneo, Marco; Podda, Gian Marco (Hepatology communications, 2022)
In patients with cirrhosis with severe thrombocytopenia (platelet count [PC] <50 × 109/L) and undergoing invasive procedures, it is common clinical practice to increase the PC with platelet transfusions or thrombopoietin receptor agonists to reduce the risk of major periprocedural bleeding. The aim of our study was to investigate the association between native PC and perioperative bleeding in patients with cirrhosis undergoing surgical procedures for the treatment of hepatocellular carcinoma (HCC). We retrospectively evaluated 996 patients with cirrhosis between 1996 and 2018 who underwent surgical treatments of HCC by liver resection (LR) or radiofrequency ablation (RFA) without prophylactic platelet transfusions. Patients were allocated to the following three groups based on PC: high (>100 × 109/L), intermediate (51‐100 × 109/L), and low (≤50 × 109/L). PC was also analyzed as a continuous covariate on multivariable analysis. The primary endpoint was major perioperative bleeding. The overall event rate of major perioperative bleeding was 8.9% and was not found to differ significantly between the high, intermediate, and low platelet groups (8.1% vs. 10.2% vs. 10.8%, P = 0.48). On multivariable analysis, greater age, aspartate aminotransferase, lower hemoglobin, and treatment with LR (vs. RFA) were found to be significant independent predictors of major perioperative bleeding, with associations with disease etiology and year of surgery also observed. After adjusting for these factors, the association between PC and major perioperative bleeding remained nonsignificant. Conclusion: Major perioperative bleeding was not significantly associated with PC in patients with cirrhosis undergoing surgical treatment of HCC, even when their PC was <50 × 109/L. With the limit of a retrospective analysis, our data do not support the recommendation of increasing PC in patients with severe thrombocytopenia in order to decrease their perioperative bleeding risk.